Parabolic and Navier–Stokes Equations 2008
DOI: 10.4064/bc81-0-16
|View full text |Cite
|
Sign up to set email alerts
|

Linear flow problems in 2D exterior domains for 2D incompressible fluid flows

Abstract: The paper analyzes the issue of existence of solutions to linear problems in two dimensional exterior domains, linearizations of the Navier-Stokes equations. The systems are studied with a slip boundary condition. The main results prove the existence of distributional solutions for arbitrary data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…), since then one may use standard techniques for Hilbert spaces. We refer the Reader to [15], where a similar linear problem is considered and using these results we are able to show existence also for the Oseen system in an elementary way.…”
Section: Proof Of Theorem 11mentioning
confidence: 85%
“…), since then one may use standard techniques for Hilbert spaces. We refer the Reader to [15], where a similar linear problem is considered and using these results we are able to show existence also for the Oseen system in an elementary way.…”
Section: Proof Of Theorem 11mentioning
confidence: 85%
“…In [13] it is shown that also for an exterior domain a family of solutions to a similar problem is also one dimensional. In that case, however, one needs to use additional property for a solution v, namely v → 0 as |x| → ∞.…”
Section: The Kernel Function ψmentioning
confidence: 97%